First autochthonous dengue outbreak in Italy, August 2020 - Lazzarini, Luca; Barzon, Luisa; Foglia, Felice; Manfrin, Vinicio; Pacenti, Monia; Pavan, Giacomina; Rassu, Mario; Capelli, Gioia; Montarsi, Fabrizio; Martini, Simone; Zanella, Francesca; Padovan, Maria Teresa; et al. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2020)
In August 2020, during the coronavirus disease (COVID-19) pandemic, five locally acquired cases of dengue virus type 1 were detected in a family cluster in Vicenza Province, North-East Italy where Aedes albopictus mosquitoes are endemic. The primary case was an importation from West Sumatra, Indonesia. This is the first outbreak of autochthonous dengue reported in Italy. During the COVID-19 pandemic, screening of febrile travelers from endemic countries is crucial in areas where competent vectors are present.